Depressive symptoms in fibromyalgia - Moreno, Vanessa (2010)
Introduction: Fibromyalgia is a common musculoskeletal problem in clinical practice and is associated with psychiatric disorders. The association with major depression potentially has therapeutic implications. Objective: To determine the prevalence of depressive symptoms in a sample of patient with fibromyalgia. Design: Observational and transversal study. Setting: Rheumatology Department, Maria Auxiliadora Hospital, Lima, Peru. Participants: Fifty-five patients of both sexes with fibromyalgia. Interventions: Fibromyalgia tender points count and use of Hamilton Rating Scale for Depression (HDRS). Main outcome measures: Percentage of depressive symptoms. Total HDRS score in relation to tender point count. Results: Average age was 54,9 ± 14 years, 80% were females, and the average tender point score was 14,4 ± 1,5. The HDRS score did not show depression mood symptoms in 32,7%, 27,7% had mild symptoms, 30,9% moderate and 9% severe symptoms. In no patient depression mood symptoms were considered very severe. There was significant correlation between the number of tender points and HDRS score (r= 0,740), p< 0,001. Conclusions: Severe or very depressive symptoms are infrequent in fibromyalgia and depression mood symptoms seem to correlate positively with the number of tender points.